Recombination of non-equilibrium charge carriers injected into Ge through intermediate defective layer - Nadtochiy, V.; Golodenko, N.; Nechvolod, N. (Functional Materials, 2005)
The recombination of non-equilibrium charge carriers injected into n-Ge sample through an intermediate defect layer has been studied in experiment as well as theoretically. The structure defects were formed by cyclic straining with simultaneous ultrasonic irradiation of the sample at 310 K. Distribution of defects in the sample depth was examined by metallography. The recombination of the injected carriers was studied by conductivity modulation in a point contact with the semiconductor surface. Two differently inclined segments have been found in plots of measuring pulse voltage decay against delay time in relation to the injecting pulse. These two segments are associated with recombination of surplus charge carriers in the subsurface defect layer and in depth of the crystal. The length and steepness of the segments at small delay time are rising with increase of the defect layer thickness and concentration of defects therein.